Apoplastic effectors secreted by two unrelated eukaryotic plant pathogens target the tomato defense protease Rcr3. - Song, J; Win, J; Tian, M; Schornack, S; Kaschani, F; Ilyas, M; van der Hoorn, R; Kamoun, S (2009)
Current models of plant-pathogen interactions stipulate that pathogens secrete effector proteins that disable plant defense components known as virulence targets. Occasionally, the perturbations caused by these effectors trigger innate immunity via plant disease resistance proteins as described by the "guard hypothesis." This model is nicely illustrated by the interaction between the fungal plant pathogen Cladosporium fulvum and tomato. C. fulvum secretes a protease inhibitor Avr2 that targets the tomato cysteine protease Rcr3(pim). In plants that carry the resistance protein Cf2, Rcr3(pim) is required for resistance to C. fulvum strains expressing Avr2, thus fulfilling one of the predictions of the guard hypothesis. Another prediction of the guard hypothesis has not yet been tested. Considering that virulence targets are important components of defense, different effectors from unrelated pathogens are expected to evolve to disable the same host target. In this study we confirm this prediction using a different pathogen of tomato, the oomycete Phytophthora infestans that is distantly related to fungi such as C. fulvum. This pathogen secretes an array of protease inhibitors including EPIC1 and EPIC2B that inhibit tomato cysteine proteases. Here we show that, similar to Avr2, EPIC1 and EPIC2B bind and inhibit Rcr3(pim). However, unlike Avr2, EPIC1 and EPIC2B do not trigger hypersensitive cell death or defenses on Cf-2/Rcr3(pim) tomato. We also found that the rcr3-3 mutant of tomato that carries a premature stop codon in the Rcr3 gene exhibits enhanced susceptibility to P. infestans, suggesting a role for Rcr3(pim) in defense. In conclusion, our findings fulfill a key prediction of the guard hypothesis and suggest that the effectors Avr2, EPIC1, and EPIC2B secreted by two unrelated pathogens of tomato target the same defense protease Rcr3(pim). In contrast to C. fulvum, P. infestans appears to have evolved stealthy effectors that carry inhibitory activity without triggering plant innate immunity.